The taxation and basic rights that carry through the rights of freedom, equality and solidarity A tributação e direitos fundamentais que realizam os valores da liberdade, igualdade e solidariedade - Marlene kempfer Bassoli (Scientia Iuris, 2005)
The phenomenon of human rights has showed up since eighteenth and ninehteenth centuries trhough the philosophical, sociological and juridical clash round of natural law doctrine. The theme evolves aceleratly after Second World War. Conquests were stricken in areas like individual, political, social, transindividual rights and, nowadays, the agenda is the right of development of the people in social, cultural, political and economical areas. A panoramic study about legal systems in different moments and different States of the contemporary history of the civilization, leads to see through that human rights were contemplated by laws, for this reason, is were brought through of the confirmation process to the juridical systems like fundamental rights. They must be protected by State and against State’s power. Considerations in the present study will must to built an interpretation that aim the constitutional owe of the Brazilian State to, through of the tributary laws, it enables conducts that confirms the values of liberty, equality and solidarity that achieve of fundamental rights. O fenômeno dos direitos humanos tem maior destaque a partir dos séculos XVII e XVIII por meio dos embates filosóficos, sociológicos e jurídicos em torno da doutrina do direito natural. O tema evoluiu de modo acelerado após a 2ª guerra mundial. As conquistas foram atingidas no campo dos direitos individuais, políticos, sociais, transindividuais e, no estágio atual, a pauta é o direito ao desenvolvimento dos povos no âmbito social, cultural, político e econômico. Um estudo panorâmico dos ordenamentos jurídicos, em diferentes momentos da história da civilização contemporânea, permite constatar que os direitos humanos foram contemplados por normas jurídicas, portanto, trazidos por meio do processo da positivação aos ordenamentos jurídicos como direitos fundamentais. Na condição jurídica de direitos fundamentais viabilizam condutas que realizam valores fundamentais. Devem ser tutelados pelo Estado e contra o poder do Estado. As considerações neste estudo serão no sentido de construir uma interpretação que aponte o dever constitucional imposto ao Estado brasileiro para, por meio das normas tributárias, viabilizar condutas que positivam os valores da liberdade, igualdade e solidariedade realizadores de direitos fundamentais.